2002
DOI: 10.1289/ehp.02110765
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke exposure and pulmonary function among adults in NHANES III: impact on the general population and adults with current asthma.

Abstract: The impact of environmental tobacco smoke (ETS) exposure on adult pulmonary function has not been clearly determined. Because adults with asthma have chronic airway inflammation, they may be a particularly susceptible group. Using data from the Third National Health and Nutrition Examination Survey (NHANES III), I examined the cross-sectional relationship between serum cotinine, a biomarker of ETS exposure, and pulmonary function among 10,581 adult nonsmokers and 440 nonsmoking adults with asthma whose cotinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 50 publications
6
68
0
1
Order By: Relevance
“…Previous pulmonary function analyses of the NHANES III data identified responses in women, but not in men, associated with serum cotinine measures of environmental tobacco smoke exposure (Eisner 2002). The magnitudes of the associations observed with MBP and MEP among men are similar to those observed for environmental tobacco smoke among women.…”
Section: Discussionmentioning
confidence: 55%
“…Previous pulmonary function analyses of the NHANES III data identified responses in women, but not in men, associated with serum cotinine measures of environmental tobacco smoke exposure (Eisner 2002). The magnitudes of the associations observed with MBP and MEP among men are similar to those observed for environmental tobacco smoke among women.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have found moderate correlations between self-reported ETS exposure and biomarker levels (e.g., cotinine) or direct personal exposure monitoring (e.g., nicotine) [33,[37][38][39][40][41][42]. We cannot, however, exclude some systematic misclassification of ETS exposure.…”
Section: Discussionmentioning
confidence: 83%
“…Based on our results, the 95% confidence intervals for the lower exposure quartiles are compatible with a substantially increased risk of COPD. Moreover, we have previously shown that very low levels of ETS exposure can exacerbate adult asthma [33]. We have also shown that moderate levels of ETS exposure are associated with impaired pulmonary function [34].…”
Section: Discussionmentioning
confidence: 93%
“…In adults, the relevant role of ETS as a risk factor for the presence of respiratory symptoms/diseases among exposed subjects was shown in epidemiological studies (Leuenberger et al, 1994;Coultas, 1998;Jaakkola, 2002), while findings on lung function impairment are less consistent (Xu and Li, 1995;Eisner, 2002). Increased indoor concentrations of PM are associated with an increased frequency of respiratory symptoms of the lower respiratory tract in children (BraunFahrlander et al, 1992;Neas et al, 1994;Qian et al, 2002) and with adverse respiratory health effects in nonsmoker adults (Xu and Wang, 1993;Venners et al, 2001).…”
Section: Introductionmentioning
confidence: 97%